2018
DOI: 10.1021/acs.analchem.8b00214
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Analysis of the Interaction between Specific Ligands and Immobilized Beta-2-Adrenoceptor by Adsorption Energy Distribution

Abstract: Although a comparatively robust method, immobilized protein-based techniques have displayed limited precision and inconsistent results due to a lack of strategy for the accurate selection of drug adsorption models on the protein surface. We generated the adsorption data of three drugs on immobilized beta-2-adrenoceptor (β-AR) by frontal affinity chromatography-mass spectrometry (FAC-MS) and site-specific competitive FAC-MS. Using adsorption energy distribution (AED) calculations, we achieved the best adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
(84 reference statements)
0
17
0
Order By: Relevance
“…When the incubating time reached 8 h, we achieved the highest expression of the receptor. Comparing with the culture of his-tagged β 2 -AR (154.1 ± 4.2 μg/mL) in LB media, , we concluded that the yield clearly increased. This was reasonable since SNAP fusion proteins are successfully and efficiently expressed on cell surface, in the cytoplasm, in the endoplasmic reticulum, and in the nucleus. , Taking inspiration from previous reports on maltose-binding protein and thioredoxin A, , we hold that SNAP is a very efficient C-terminal fusion partner guiding the expression into the inner membrane; introduction of SNAP into GPCRs will give functional expression of lipid embedded receptor.…”
Section: Resultsmentioning
confidence: 74%
“…When the incubating time reached 8 h, we achieved the highest expression of the receptor. Comparing with the culture of his-tagged β 2 -AR (154.1 ± 4.2 μg/mL) in LB media, , we concluded that the yield clearly increased. This was reasonable since SNAP fusion proteins are successfully and efficiently expressed on cell surface, in the cytoplasm, in the endoplasmic reticulum, and in the nucleus. , Taking inspiration from previous reports on maltose-binding protein and thioredoxin A, , we hold that SNAP is a very efficient C-terminal fusion partner guiding the expression into the inner membrane; introduction of SNAP into GPCRs will give functional expression of lipid embedded receptor.…”
Section: Resultsmentioning
confidence: 74%
“…The use of the above equation requires a set of initial estimation of F(E i ) as the method maximizes the influence of data over the final distribution. The initial guess used to determine the site energy distribution function is based on the 'total ignorance' guess: [72][73][74] (57)…”
Section: Expectation-maximization Methodsmentioning
confidence: 99%
“…Recently, the method was successfully used for protein-ligand screening. 74 With sufficient number of iterations, this method can unambiguously discriminate different types of adsorption sites having energy difference of less than 4-5 kJ/mol. 75 The main limitation of this method is that it cannot distinguish between the adsorption sites having energies less than 2 kJ/mol.…”
Section: Expectation-maximization Methodsmentioning
confidence: 99%
“…FAC–MS has been employed to assess the adsorption data of three drugs (salbutamol, terbutaline, and pseudoephedrine) and the beta-2-adrenoreceptor (β 2 -AR) attached to polystyrene amino microspheres (Li et al, 2018). Adsorption data of the selected drugs obtained by FAC–MS and site-specific studies have helped to investigate the adsorption models for the binding of each ligand through adsorption energy distribution calculations.…”
Section: On-line Approachesmentioning
confidence: 99%